Small touches to big walks-the impact of rehabilitation on Sjögren-Larsson syndrome: A case report - YOLCU, GÜNAY; KENİŞ COŞKUN, ÖZGE; KARADAĞ SAYGI, NAİME EVRİM (My University, 2022)
© 2022-IOS Press. All rights reserved.Sjögren-Larsson syndrome (SLS) is a rare neurocutaneous disorder characterized by the presence of congenital ichthyosis, spasticity, and mental retardation. As with other rare genetic diseases, treatment is mainly symptomatic. Due to the absence of definitive treatment, lifelong follow-up and support of patients are important to improve the quality of life. A 7-year-old female child who was diagnosed as having SLS was referred to the rehabilitation clinic. After 20 sessions of a rehabilitation program, she started walking independently with the additional contribution of ankle-foot orthoses (AFOs). The contribution of the short-term rehabilitation approach and especially the administration of AFOs to the independence level of the patient is emphasized herein.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Rehabilitasyon; Pediatrics, Perinatology and Child Health; Physical Therapy, Sports Therapy and Rehabilitation; Rehabilitation; Orthosis; rare disease; rehabilitation